Homegrown Internationalism? Challenging Epistemic Dialogue in Africa's Development Cooperation - Matthew Sabbi (Africa Spectrum)
Homegrown concepts are increasingly viewed as indigenous alternatives to challenge long-standing Western hegemony in development co-operation and insert non-Western agency. Drawing on two African cases from Ghana and Rwanda, this article develops a framework to demonstrate the strategic ambiguity as Global South states seek influence in their international encounters. While the two countries closely follow the existing logic of development co-operation, they subtly challenge its dominant epistemology. Rwanda's Imihigo -driven donor self-assessment forum and Ghana's Sankofa -informed diaspora investment forum are two cases of similar but different concepts that typify the simultaneous coupling of indigenous and co-operation norms for international leverage. Together, they highlight the power and limits of homegrown concepts to drive the South's agency in the international arena of co-operation.